Freight transport in Brussels and its impact on road traffic? - Philippe Lebeau; Cathy Macharis (Brussels Studies)
Car traffic is one of the biggest problems faced by sustainable development in the Brussels Region. While the debate regarding the use of cars in the city is important, noise pollution caused by goods vehicles is mentioned much less often. They are responsible for 25% of CO2 emissions, 33% of PM2.5 emissions and up to 32% of PM 10 emissions caused by road transport in the capital. Given that a significant increase in freight transport is predicted, it is necessary to examine this lesser known aspect of mobility in Brussels. The aim of this article is therefore to establish a diagnosis of freight transport in Brussels. The different available sources are brought together in order to better understand the sector’s dynamics. Some of the solutions implemented in the Region to improve the sustainability of delivery operations are also presented.